Analysing irrigated crop rotation patterns in arid Uzbekistan by the means of remote sensing: A case study on post-Soviet agricultural land use. (January 2016) - Conrad, C.; Lamers, J.P.A.; Ibragimov, N.; Löw, F.; Martius, C.
Abstract: In Central Asia, actual cotton rotation practices are repeatedly believed to resemble "Soviet cropping conditions" with continuous cotton sequences of six years or more. We investigated current cotton growing patterns in Khorezm, one representative cotton production region in Uzbekistan utilizing time series of 250-m MODIS satellite data. A Random Forest model was established using reference data of 2004–2007 to generate annual crop maps in 2000–2009. A linear model was applied to assess the spatial distribution of the longest observed cotton sequence within the ten-year observation period. All cotton-growing sequences were compared to the national crop rotation recommendations. The classification achieved an overall accuracy of 82%. We found that cotton remains the major crop in the region. It was cultivated for more than five out of the ten years on 46.5% of the cropland. But "Soviet cropping conditions" on less than 20% and officially recommended cotton sequences on more than 50% of the cropland challenge the notion that cotton mono-crop dominates Central Asia. Statistical analysis revealed that long cotton sequences preferably occur on fields far from settlements and under reduced soil suitability for irrigation. The results enable decision makers to better explain unfavourable cotton cultivation practices and to stimulate improvements. Highlights: Cotton rotations in the Khorezm irrigation system of Uzbekistan were analyzed. Cotton sequences were extracted from annual MODIS classifications (2000–2009). Short cotton sequences (max. 3 years) occurred frequently in settled areas. General statements on post-Soviet cotton cultivation are challenged. GIS analysis shows areas of cotton monocropping, focal points for improvements.